Inhibitors of e-Government adoption: Determinants of habit and adoption intentions - Manuel Rey-Moreno; Cayetano Medina-Molina (Journal of Innovation & Knowledge (JIK), 2017)
Explanatory models of e-Government adoption are based on the premise that user behavior results from users' intentions, which derive from users' beliefs and attitudes. According to such models, citizens' high intentions to use e-Government tools should have led to the widespread adoption of these tools. Yet this has not occurred. Therefore, existing models fail to explain the adoption of e-Government. These models must be complemented to explain the cause of citizens' failure to adopt e-Government. Attempts to build a satisfactory model include the design of dual models (jointly analyzing facilitators and inhibitors) and integrating models (jointly analyzing the interaction between intention and habit in prompting behavior). This study identified several inhibitors of e-Government adoption. Organizational support, self-efficacy, benefits, loss aversion, regret aversion, control, transition costs, sunk costs/switching costs, uncertainty, habit, resistance, and inertia were found to inhibit citizens' adoption of e-Government.
Keywords: H44; M15; M38; M31; O31; O32; 650; e-Government; Inhibitors; Resistance; Habit; Inertia